Экспериментальное определение активного сопротивления и электропроводности сильноточного плазменного канала в разрядной цепи генератора импульсной компоненты тока искусственной молнии - Баранов, М.И.; Колиушко, Г.М.; Лысенко, В.О. (Електротехніка і електромеханіка, 2011)
Approximate numerical values are experimentally obtained for linear ohmic resistance and specific conductivity of a heavycurrent plasma channel of an air spark discharge in the loop of a powerful capacitive storage applied for artificial lightning current pulse A-component formation with the rated magnitude not less than 200 kA.